2004
DOI: 10.1021/jm040812w
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Staphylococcus aureus Methionine Aminopeptidase Complexed with Keto Heterocycle and Aminoketone Inhibitors Reveal the Formation of a Tetrahedral Intermediate.

Abstract: Chem. 2002, 67, 3637-3642) suggested that structures attributed by us to 4a, 4d, 7a, and 7d are incorrect. Our own re-investigation led us to conclude that compounds 4a, 4d, 7a, and 7d have aza-bicyclo[3.2.2]nonane structures as depicted in the accompanying graphic. These revised structures have been confirmed by NMR and X-ray analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…Structures of dimetalated and trimetalated MetAP in complex with non-peptidic inhibitors are abundant in literature 11,12,34,39,40 . When a high metal concentration is used in inhibitor screening, the condition favors formation of dimetalated MetAP, and the screening tends to identify inhibitors that require extra metal ions for affinity.…”
Section: Design Of Metap Inhibitors For Efficacy In Cellsmentioning
confidence: 99%
“…Structures of dimetalated and trimetalated MetAP in complex with non-peptidic inhibitors are abundant in literature 11,12,34,39,40 . When a high metal concentration is used in inhibitor screening, the condition favors formation of dimetalated MetAP, and the screening tends to identify inhibitors that require extra metal ions for affinity.…”
Section: Design Of Metap Inhibitors For Efficacy In Cellsmentioning
confidence: 99%
“…Fumagillin, a natural product, and its analogues are a unique class of MetAP inhibitors that covalently modify a conserved histidine residue at the active site (H79 of E. coli MetAP, and the equivalent H231 of human type II MetAP) [ 9 , 15 , 16 ]. Several classes of non-peptidic and reversible MetAP inhibitors have been identified recently, such as furancarboxylic acids [ 17 , 18 ], thiabendazole and other thiazole-containing compounds [ 17 , 19 - 21 ], triazole-based derivatives [ 22 - 24 ], and sulfonamides [ 25 , 26 ]. However, structural analysis of these nonpeptidic inhibitors in complex with MetAP showed that inhibition by many of the thiazole and triazole-containing compounds and sulfonamides is metal-mediated, and they bind to the active site of enzyme through a divalent metal ion with one of the conserved active site histidines (most with H97, and some with H181; both are E. coli MetAP numbering) [ 19 , 21 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several classes of non-peptidic and reversible MetAP inhibitors have been identified recently, such as furancarboxylic acids [ 17 , 18 ], thiabendazole and other thiazole-containing compounds [ 17 , 19 - 21 ], triazole-based derivatives [ 22 - 24 ], and sulfonamides [ 25 , 26 ]. However, structural analysis of these nonpeptidic inhibitors in complex with MetAP showed that inhibition by many of the thiazole and triazole-containing compounds and sulfonamides is metal-mediated, and they bind to the active site of enzyme through a divalent metal ion with one of the conserved active site histidines (most with H97, and some with H181; both are E. coli MetAP numbering) [ 19 , 21 , 25 ]. It has been pointed out that formation of such complexes may be an artefact during crystallization or in in vitro assays using high metal concentrations [ 14 , 19 , 27 ], and whether there are enough free metal ions available inside cells to form such inhibitor-enzyme complexes is a question.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, inhibition of all three human MetAPs was beneficial in killing cancer cells . Several studies have been directed at finding inhibitors of these enzymes . However, owing to the similarity in the active sites among all MetAPs, achieving selectivity with small molecules between the type I and type II enzymes is difficult .…”
Section: Introductionmentioning
confidence: 99%